Ministério público: da importância da atuação educativa, proativa e resolutiva junto à sociedade regional: análise interdisciplinar e humanística do projeto “aprendendo direito e resgatando cidadania” do Ministério Público do Tocantins - Lira, Vera Nilva Alvares Rocha (Universidade Federal do Tocantins, 2023)
ABSTRACT With the passage of the last three decades and the appearance of new social values, the Public Ministry was required to adopt an adequate posture to demand the concreteness of fundamental collective rights and unavailable individuals. With the advent of the Federal Constitution of 1988, stipulating the fundamental objectives of the Federative Republic of Brazil in its art. 3rd, this demand for a change in profile was undoubted. Indeed, linked to those fundamental objectives, it should migrate from an adversarial or competitive profile to a consensual or collaborative one, striving, as a rule, for proactive dialogue and the application of self-compositional methods, instead of always delegating the resolution to another public body, using instruments judicialization as the only way to resolve social conflicts or controversies. In this context of post-positivism and under the aegis of neoconstitutionalism, where the Federal Constitution came to be located, with its tentacles of mandatory normativity, at the center of the entire legal system, the Public Ministry assumed the identity of a proactive and resolving body, acting on all fronts, with a view to social interest, as is the case with educational issues of citizenship and human rights. Therefore, under the guidance of the National Council of the Public Prosecutor's Office and the launching of a National Policy to Incentive Self-Composition, several methods and instruments are needed to fulfill the task, an example of mediation, negotiation, public civil investigation, recommendation, term behavior adjustment and, equally, social projects, generally in partnership with other bodies. In this iter, in Tocantins, in 2013 and 2014, the Public Ministry designed and implemented, in partnership with the State Department of Education, Youth and Sports, together with secondary schools in Palmas, Gurupi and Colinas do Tocantins, the Project “Learning Law and Redeeming Citizenship”. Throughout the research, embodied in this technical report, the importance of the educational, proactive and resolute action of the Public Prosecutor's Office as a way of maintaining social legitimacy and a project linking its effectiveness is addressed.